The evaluation of the curriculum design of Bachelor's Degree in Modern Languages, specialization in French and English: the perspectives of curriculum changes - Aguilar de Barrientos, Karen Astrid; Palomo López, Génesis Briguitte (2024)
RESUMEN: Para realizar este trabajo, se llevó a cabo una investigación cualitativa en la que se utilizaron tres instrumentos diferentes para obtener los resultados de esta misma, un análisis de contenido para evaluar el diseño del plan curricular, un cuestionario de preguntas semi abiertas para indagar lo que los profesores piensan, cambian y sugieren basado en lo que conocen sobre el diseño del plan curricular, y un cuestionario para saber lo que los estudiantes consideran pueda cambiarse desde su punto de vista y experiencia en la licenciatura. Además de eso, se requería investigar sobre los diferentes tipos de planes de estudio para aprender un idioma extranjero con el propósito de analizar los diferentes programas en el diseño curricular tomando en cuenta 7 criterios: descripción general, objetivos, descripción del curso, metodología, contenidos, evaluación y bibliografía. Luego, basado en la información obtenida en el análisis de contenido, los otros instrumentos se llevaron a cabo con la población. Éstos se analizaron individualmente, y luego la información proporcionada por los estudiantes y maestros se comparó con los datos en el análisis de contenido, dando como resultado que tanto los profesores como los estudiantes concuerdan hacer algunos cambios en el diseño del plan curricular. Tomando estos resultados como base, basado en las opiniones de los estudiantes y profesores, se podría hacer otra investigación con el propósito de proporcionar un plan de acción para implementar los posibles cambios que ayuden a mejorar el desarrollo de los estudiantes de lenguas modernas. ABSTRACT: This research is made with the purpose of finding out the different syllabi present in the curriculum design, and the most suitable changes that could be done to this. In order to improve students’ background after finishing their studies in the Bachelor’s Degree. To achieve that, qualitative research was carried out where two different instruments were used to obtain the research results. A content analysis to evaluate the curriculum design, and questionnaires to inquire what teachers suggest based on what they know about the curriculum design, and also to know what the students consider to be changed from their point of view and experience in the Bachelor’s Degree. Besides that, it was required to inquire about the different kinds of syllabi for learning a foreign language with the purpose of analyzing the different programs in the curriculum design considering 7 criteria: overview, objectives, course description, methodology, contents, assessment, and bibliography. Then, based on the information obtained in the content analysis, the other instruments were conducted with the population. These were analyzed individually, and then the information provided by students and teachers was compared with the data in the content analysis, giving as a result that both teachers and students agree to make some changes to the curriculum design. Taking these results as a basis, based on students and teachers’ opinions, another research could be made in order to provide a plan of action to implement the possible changes that help to improve the development of modern languages students